The Effect Of Dividend Per Share And Profitability On Stock Prices: Evidence From Panel Data Of Property And Real Estate Companies Listed On The Indonesia Stock Exchange (2019–2023) - Vina Nur Afni; Ita Rahmawati; Lailatus Sa’adah (International Journal of Economics and Development, 2025)
This study investigates the effect of Dividends per Share (DPS) and profitability on the stock prices of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. From a population of 92 companies, 7 were selected as research samples through purposive sampling based on specific eligibility criteria. The research employs a quantitative approach with an associative design to examine the relationship between the variables. Secondary data were obtained from published financial statements, and the analysis was conducted using panel data regression with E-Views 12 software. The results reveal that DPS exerts a significant positive influence on stock prices, indicating that dividend distribution is a key factor in attracting investor interest and enhancing market value in the property and real estate sector. Conversely, profitability, as measured by Return on Assets (ROA), does not significantly affect stock prices, suggesting that investors may place greater emphasis on dividend policies rather than operational profitability when making investment decisions in this industry. These findings contribute to the literature on capital market behavior in emerging economies and offer practical implications for corporate managers in formulating dividend strategies to strengthen investor confidence and market performance.